SELECTION SYSTEMS IN THE PRESIDENTIAL GOVERNMENT SYSTEM: STABILITY OF STATE REGIONAL SELECTION SYSTEM IN MANAGEMENT AND EVALUATION OF JUDICIAL CRITERIA - Berat AKINCI (Fırat University, 2019)
The Presidential Government System, adopted by the April 16 referendum, will actually be implemented with the elections to be held in 2019. There is no doubt that stability in government has an important place in the story of Turkey's transition to a new government system. Turkey, which has not been able to achieve the goals it wants with the coalition governments for years, has realized that it can not reach these targets without stability in the administration. However, the stability that will be provided by the new government system is also important in terms of the success of the system, which is also provided in life. At this point, it seems that there is a growing debate on the need to change the election system in coordination with the new system. In this context, the electoral systems, which have a very wide range of influence from the determination of the parliaments in representative democracies to the shaping of the power, remain uncertain as to how the constantly changing balance between stability in administration and representation in justice will be in the new government system. Despite the fact that many different election systems have been applied daily, especially since the passage of a multi-party system in Turkey, the fact that the discussions on the electoral systems have never been completed stem from the fact that the best answer can not be given for stability in administration or justice in the case of representation. While not being the best answer to this question, each country has chosen the way to implement its electoral systems that reflect its own circumstances. Our electoral system experience, which started in 1946 with a list-based majority system, has been constantly changing day by day with elections in which proportional and mixed systems are applied. In this change, the parties usually keep their interests on the front, while the approaches that reveal the countrymen are passed. Although there is no result created by the electoral systems alone, the stability of the administration has not been achieved except for certain periods in our country, and the stability has been ignored in the case of justice. Therefore, it is of utmost importance that the narrow regional electoral system, which stands out in terms of ensuring the stability that will be provided in the administration in the Presidential Government System, is designed to provide justice to the representatives. In this study, if the narrow regional electoral system is implemented with the new government system, it will be evaluated how soon the justice in the representation and the stability in the administration can be achieved. Ultimately, the changes to be made in the electoral systems should be preceded by maximizing stability in justice and governance, taking the social and political conditions of our country into consideration, in order to reinforce the success of the new government system.